An Investigation of Factors Affecting Waste in Defense Systems Acquisition System - Hamid Reza Fartouk Zadeh; Javad Vaziri (بهبود مدیریت, 2011)
Two main strategies of defense BPR (innovation strategy and capacity organizing strategy) follow innovative foundation for defense industry that is made of powerful Entrepreneurship Nuclei and Collaborative R&D Networks across the country. Deploying these strategies depends on Financial Capability. Waste as something that takes Financial Capability to interlunar is investigated in this research. The research reviews the concept and importance of Financial Capability then presents a conceptual framework for waste life cycle. Furthermore based on this framework, factors affecting waste in each stage of the life cycle would be identified and tested by using survey. Finally, some suggestions for confronting waste at each stage are provided.